(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2019)
An infestation of rodents in a healthcare facility is especially dangerous because these pests can carry disease and spoil food with the bacteria and viruses they harbor in their saliva and droppings. Exposure to dangerous pathogens could be disastrous for already health-compromised patients. The aim of the study is to implement an integrated control program for rodents inside hospitals and to clarify the most important preventive methods that can be used in the control process and to make some important observations in the application of methods of integrated control of rodents to obtain the best program for rodent control in hospitals.